Comparing the Effectiveness of group Dialectical Behavior Therapy and Solution-Focused Brief Therapy on Self-Esteem, Cognitive-Emotional Regulation and Non-Suicidal Self-Injury in daughters - Ghazal Yasfard; Zahra Abaspour Azar; Seyed Ali Hosseini Almadani (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: Today, self-injury behavior has a significant outbreak among adolescents. The purpose of the present study was to compare the effectiveness of dialectical behavior therapy (DBT) and solution-focused brief therapy (SFBT) on self-esteem, cognitive emotion regulation, and non-suicidal self-injury behavior. Materials and Methods: This study was semi-experimental research. The statistical population consisted of 45 students studying in junior high school in Pardis city (2017-2018). They were committed non-suicidal self-injury behavior at least for once. Using random access sampling method, the sample divided into two experimental groups and a control group (n1 = n2 = n3 = 15). The research tools included Eysenck's self-esteem questionnaire (1976),  Garnefski and Kraaij's cognitive emotion regulation questionnaire (2006), and Klonowski and Glenn's self-injurious behaviors and functions (2009). Experimental groups were under the dialectical behavior therapy and solution-focused (brief) therapy. The data were analyzed using multivariate analysis of covariance. Results: There was a significant difference between the effectiveness of dialectical behavior therapy with solution-focused brief therapy on reducing self-injury behavior (p <0/001) and cognitive emotion regulation (p<0/05). There wasn't any significant difference in self-esteem variable. The mean scores of self- injury behavior for the dialectical behavior therapy group in post-test was significantly lower than the mean scores of the solution-focused brief therapy group and the control group. The mean of the dialectical behavior therapy group after a positive reappraisal was significantly higher than the mean of the control group. Conclusions: The method of dialectical behavior therapy compared to Solution-focused therapy has a greater impact on increasing the positive reappraisal subscale in cognitive emotion regulation and decreasing self-injury behavior.